Quality of Life in Patients with Premature Ventricular Contraction: A single-center study in Iran - Sarmastzadeh, Tala; Sarmastzadeh, Elnaz; Safi, Morteza; Akbarzadeh, Mohammad Ali (Novelty in Biomedicine, 2023)
Background: Premature ventricular contraction (PVC) symptoms have a direct relationship with, hospitalization and cardiovascular mortality, and finally, the quality of life of patients. The difference in the quality of life between men and women in different arrhythmias has been reported. In this study, the quality of life of PVC patients was evaluated using the arrhythmia-specific questionnaire in tachycardia and arrhythmia (ASTA) questionnaire Methods: A cross-sectional study was conducted on 200 patients with PVCs who were referred to the heart clinic of Modares Hospital in Tehran in 2019. The demographic characteristics and evaluation of the patient's symptoms were recorded through the ASTA questionnaire. The relationship between the answers to the questionnaire and the gender of the patients was measured with statistical tests. Results: 200 patients with abnormal ventricular contraction (88 females and 112 male PVC) with an average age of 16.4 ± 52.7 years (minimum 25 years and maximum 85 years) were studied. The chi-square test did not show a significant relationship between the questions of the ASTA questionnaire and the gender of the patients. Conclusion: The findings of this study show that quality of life and ASTA questionnaire items in PVC patients have no significant relationship with the gender of this category of patients.